Of Self and Polity: Writing Resistance in Dixit’s Madhavi - Phuyal, Komal Prasad (Literary Studies, 2022)
Madan Mani Dixit’s novel Madhavi (1983) subtly argues for change in the existing rigid political order of his time by projecting self larger than the polity. Borrowing a narrative from the Mahabharata, the novelist develops it into a full length novel to point out the cracks in the political system of his time: as a political order, the Panchayat had lost the sense of justice within the first two decades after its promulgation in 1962. Dixit employs Galav and Madhavi as dissenting voice of the age, upholding the spirit of resistance and seeking for transformation in consciousness. The tale from the post-Vedic society serves as an instance to imply the parallel situation of the country that attempts to transcend beyond the contemporary context. In this study, I have approached the novel from the new historicist vantage point to dissect the text in the changing political context of its writing. The paper claims that as a Nepali novel, Dixit’s Madhavi rewrites the episode of political struggle between the person and polity in an oppressive political order in the 1970s in Nepal when the political self and polity were in tension as the outcome of their struggle for a new order in society. Moving beyond the existing situation, the maestro novelist picks the narrative of Madhavi and Galav from the Mahabharata and sets them in quest of new order in the form of agrarian society from the crumbling order of slavery. Dixit’s work critiques the limitations of both self and polity in leaving the impact of one on the other, thereby exposing the brutal treatment and fall of an oppressive political order. This paper reads historical reality of the 1970s in Dixit’s Madhavi in which the author writes the political history of Nepal.